Ableist and Non-Ableist Meaning Making of Internet Memes from the Lens of Systemic Functional Linguistics (SFL) - Ihsan Ramadhan; Agung Ginanjar Anjaniputra (Universitas Islam Negeri Palopo, 2025)
This study examines the meaning-making role of speech functions, through the lens of Systemic Functional Linguistics (SFL), in constructing ableist and non-ableist representations in disability-related internet memes. While memes can act as a powerful social and cultural communication medium, most research focuses on memes in general, with little attention to the representation of specific issues, particularly concerning disability. Using a mixed qualitative and quantitative approach, this study analyzed 173 clauses from 90 memes. This study aims to answer how meaning-making is realized in memes about disability and the extent to which the memes attend to the social model of disability and ableism. Findings reveal a predominance of speech roles giving information, 77%, primarily through declarative statements. However, a closer looks within these statements shows 49% clauses containing ableist content, while 51% clauses are non-ableist or neutral. Moreover, speech roles demanding good and service appear less frequently about 13% which indicates a gap between critique and real advocacy. This divided representation, coupled with the scarcity of action-oriented discourse, suggests that while memes can raise awareness and challenge some ableist narratives, a significant portion of meme still reinforces harmful stereotypes. Consequently, the current meme medium is insufficient to fully realize inclusive education or an inclusive society, as ableist content can make it harder for attitudes to change and reflect persistent societal discrimination.